Higher Order Thinking Skills in Evaluation of IV Grade Thematic Materials in Elementary Schools - Lina Novita; Tustiyana Windiyani; Elly Sukmanasa; Ridha Lugiana Utari (Universitas Pendidikan Ganesha, 2023)
Teachers still experience difficulties and are not optimal in compiling HOTS-based questions, so students' critical thinking skills become less than optimal. This study aims to develop higher-order thinking skills or Higher Order Thinking Skills known as HOTS. The type of research used is R&D with qualitative and quantitative approaches. The development model using Martin Tessmer's model consists of the Preliminary, Self-Evaluation, and Prototyping Stage. The method used in collecting data is a questionnaire. The instrument used in collecting data is a questionnaire. Questions and validation tests were carried out on 2 lecturers and 2 teachers. The trial is limited to 10 students, and the test is broad for all fourth-grade students. Data analysis techniques using qualitative and quantitative descriptive analysis. The study results prove that the questions developed are suitable for learning. Therefore, it can be concluded that research on the development of Higher Order Thinking Skills or HOTS on thematic questions is appropriate for use in learning in grade IV of elementary schools. Thinking Skills or HOTS on thematic questions are appropriate for learning in grade IV of elementary school.